The Participation of Lampulo Community in Marine Conservation Management Efforts at Fish Auction Place Lampulo Area, Banda Aceh City - Furqan, Furqan; Khairani, Yuli; Surya, Erdi; Ridhwan, M; Armi, Armi; Muchsin, Muchsin; Rimadeni, Yeni; Noviyanti, Anita (Universitas Serambi Mekkah, 2021)
This study has been conducted with the participation of Lampulo Community inmarine conservation efforts at the Fish Auction Place of Lampulo area, Banda Aceh. The population in this study was the entire fishing communityat Fish Caution Place in Lampulo area. Whereas, the samples in this study were 20 people including 16 people of fishing community, one boat commander-in-chief, one village chief, one village secretary, and one sea commander. The instruments in this research were interviews and questionnaires. Data collected through interviews and questionnaires showed that the level of participation by communities in marine conservation efforts wasin good categories and the management without any existing rules, written or unwritten rules. They utilized the mangrove forest to avoid cut down.Fishing was prohibited from using toxins that could harm marine ecosystems. Frequently, community-related to Lampulo area was held on a large scale to preserve the resources of the fishing community. Counseling about the importance to keep the conservation of the oceans at bay was often carried out. Fishermen also looked forward to both tooling and infrastructure in the management of marine conservation so that the sea will be kept in good conditions. Keywords: participation, management, ocean, conservation.